1997
DOI: 10.1007/bf02298042
|View full text |Cite
|
Sign up to set email alerts
|

Subjective work noise: A major risk factor in myocardial infarction

Abstract: The relationship between subjective work noise exposure and the risk of myocardial infarction (MI) was assessed in a population based case-control study. 395 MI patients (31-65 years) were compared to 2148 controls from a random population sample with the same agelsex distribution. The relative risk (RR) for MI-adjusted for control variables (smoking, age, social status, etc.)-was found to increase significantly and steadily with noise category. Subjective work noise exposure was the second greatest risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 8 publications
3
45
0
2
Order By: Relevance
“…If annoyance and stress-related health effects are associated, and taking into account that the observation threshold for annoyance in offices is much lower than that for industrial situations, we hypothesize that the observation threshold for noise-induced risk for hypertension in office workers is about 30 dB(A) lower than that for hypertension in blue-collar workers. The data in more recent publications on cardiovascular effects from exposure to noise are not in disagreement with the previous findings (51)(52)(53). However, one must be careful interpreting the results of these studies, as either noise measurements or proper control groups are lacking or the size of populations studied is small.…”
Section: Noise-induced Hearing Impairmentsupporting
confidence: 66%
“…If annoyance and stress-related health effects are associated, and taking into account that the observation threshold for annoyance in offices is much lower than that for industrial situations, we hypothesize that the observation threshold for noise-induced risk for hypertension in office workers is about 30 dB(A) lower than that for hypertension in blue-collar workers. The data in more recent publications on cardiovascular effects from exposure to noise are not in disagreement with the previous findings (51)(52)(53). However, one must be careful interpreting the results of these studies, as either noise measurements or proper control groups are lacking or the size of populations studied is small.…”
Section: Noise-induced Hearing Impairmentsupporting
confidence: 66%
“…If the exposure is of sufficient intensity and unpredictability, cardiovascular and hormonal responses can appear, including increases in heart rate and peripheral vascular resistance and changes in blood pressure, blood viscosity, and blood lipids. These effects are of interest because of noise-related IHD (181). Many studies in occupational settings have indicated that workers exposed to high levels of industrial noise for 5-30 years have increased blood pressure and statistically significant increases in risk for hypertension, in comparison with workers in reference areas (182).…”
Section: Circulatory Diseasesmentioning
confidence: 99%
“…Workplace noise Ising et al (1997) reported a signi®cantly elevated risk of myocardial infarction with increasing workplace noise category (electric lawnmower: RR 1.4; electric drill: RR 2.0; road drill: RR 3.8). A possible pathway of this increased risk could be via increased sympathetic stimulation, due to the exposure to high levels of the noise.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace noise: Workplace noise was assessed using a question developed by Ising (1997):``Please indicate the level of noise which matches best with the noise level at your workplace: (1) refrigerator; (2) typewriter; (3) electric lawnmower; (4) electric drill; (5) road drill''. Because of small numbers, especially in the higher categories, we combined the two lowest noise classi®cations [both estimated as 55 dB(A)], into a low-level category, and the highest three noise levels [estimated as 75, 90 and 100 dB(A)] into a high noise category.…”
Section: Personal and Work Characteristicsmentioning
confidence: 99%